Identifying Sibutramine in Slimming Herbs Sold Online - Rina Kurniaty; Fachruniza, Yunda; Rahmayani, Nabila (JURNAL BIOSAINS, 2025)
Obesity is defined as the presence of abnormal amounts of body fat and is a risk factor for diabetes and can increase the risk of hernias, varices and arthroses in the knees and feet. Consumption of slimming herbs is widely used to reduce this obesity. Slimming herbal products in their ingredients or compositions contain simplisia derived from medicinal plants and have pharmacological effects. According to the Minister of Health Regulation No. 007 of 2012 concerning the registration of traditional medicines, herbs circulating in the community must meet various requirements, one of which is that they must not contain drug chemicals, narcotics or psychotropic substances and other materials that based on health considerations and research can endanger health. Sibutramine is a weight loss drug that is often used, belongs to the class of hard drugs and can only be used based on a doctor's prescription because it can increase blood pressure. The identification of sibutramine in this study was carried out qualitatively using thin layer chromatography (TLC) method, to determine the presence or absence of the addition of drug chemicals in slimming herbs sold online. The mobile phase used was methanol (p): chloroform (p) (4:1) solvent with silica GF 254 stationary phase. The results of the study showed that two of the five slimming herbs sold online contained sibutramine with the Rf value of herbal medicine A = 0.86 and herbal medicine B = 0.91.